Ecodesign - Barbero, Silvia; Cozzo, Brunella ([Place of publication not identifed] : H.F. Ullmann Publishing, 2012)
A washing machine that purifies waste water; a photovoltaic catamaran; modular shoes that adapt to each season; a wedding dress made of starch; toys made of corn: from the means offered to us by nature to the most sophisticated technology, ecodesign combines the most innovative, captivating and original examples sustainable design.
What is ecodesign? -- Ecodesign approaches -- Household appliances -- Furniture -- Light and energy -- Transportation -- Clothing & accessories -- Toys -- Packaging -- Graphic design.
Keywords: INDUSTRIAL DESIGN -- ENVIRONMENTAL ASPECTS